2015
DOI: 10.1103/physrevb.91.115130
|View full text |Cite
|
Sign up to set email alerts
|

Spin and thermal conductivity of quantum spin chains and ladders

Abstract: We study the spin and thermal conductivity of spin-1/2 ladders at finite temperature. This is relevant for experiments with quantum magnets. Using a state-of-the-art density matrix renormalization group algorithm, we compute the current autocorrelation functions on the real-time axis and then carry out a Fourier integral to extract the frequency dependence of the corresponding conductivities. The finite-time error is analyzed carefully. We first investigate the limiting case of spin-1/2 XXZ chains, for which o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 121 publications
(226 reference statements)
10
82
0
Order By: Relevance
“…We thus propose that whenever such a plateau is present in D(t), the cleanest way of computing σ reg (ω) is the L-independent FT, in line with the reasoning of Refs. [64,67,84]. Figure 6 shows data for U/t h = 4 as an example for a case, in which no clear plateau in D(t) can be resolved with the accessible system sizes.…”
Section: Optical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We thus propose that whenever such a plateau is present in D(t), the cleanest way of computing σ reg (ω) is the L-independent FT, in line with the reasoning of Refs. [64,67,84]. Figure 6 shows data for U/t h = 4 as an example for a case, in which no clear plateau in D(t) can be resolved with the accessible system sizes.…”
Section: Optical Conductivitymentioning
confidence: 99%
“…The Q i = l q l,i are commonly ordered by their range, i = 1 corresponding to particle number Q 1 = N and i = 2 corresponding to the Hamiltonian Q 2 = H. Q 3 has range three (i.e., q l,3 involves operators acting on three neighboring sites) and has the same structure as the energycurrent operator, yet the two differ in the prefactor of one term [18]. As a consequence, thermal transport in the one-dimensional Hubbard model is ballistic at any finite temperature T > 0 [18,19]. Recently, it has been shown that there are also quasi-local conserved quantities in Bethe-ansatz integrable systems which can be crucial for some transport channels [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of superdiffusive transport in the presence of interactions and disorder is in striking contrast to the behavior of clean systems where integrability breaking terms normally lead to diffusion (for spin systems, see Refs. [41][42][43][44]). However, a simple estimate of the mean free time of scattering from the external potential gives a time-scale of τ ∼ 1/λ 2 , which is about τ ≈ 16 for the smallest λ we study and is comparable to our maximal simulation times.…”
mentioning
confidence: 99%
“…The pioneer theoretical result indicated a diffusive spin transport of the spin-1 chain system, which is a non-integrable model [52]. On the other hand, some recent theories also suggested a more complicated spin transport behavior in spin-1/2 ladders [53][54][55][56][57]. It is possible that this system could exhibit large bust diffusive spin thermal conductivity.…”
Section: Heat Transport In S = 1/2 Spin Laddermentioning
confidence: 99%
“…However, theoretical studies on the thermal conductivity of spin-1/2 ladders are rather controversial [52][53][54][55][56][57]. On the one hand, the spin-1/2 ladder is believed to have the essentially same as the spin-1 chain in the aspects of the spin-liquid ground state and the gapped magnetic spectrum.…”
Section: Heat Transport In S = 1/2 Spin Laddermentioning
confidence: 99%